Pengembangan Soal Penalaran Tipe TIMSS Menggunakan Konteks Budaya Lampung - Tri Wahyudi; Zulkardi Zulkardi; Darmawijoyo Darmawijoyo (Didaktik Matematika, 2016)
The aimed of this research is to result TIMSS-like mathematics problem type reasoning in junior high school with Lampung cultural as a context. This research involved 28 students of grade VIII A in SMP Kartika II-2 Bandar Lampung. Design research type development study chosen as method of this research which consist of two main phases namely preliminary and formative evaluation. The result of this study are 14 problems of TIMSS-like mathematics problem type reasoning with Lampung cultural as a context were valid, practice and have a potential effect. The result show that 51% reached analyze level, 38% reached integrate level, 47% reached evaluate level, 21% reached draw conclusion level, 58% reached generalize level, and 30% reached justify level. Overall, students ability of all domains on the average 41 %